On Drafting a New Architectural Syntax: Case Study of the Great Mosque of Algiers - Adli, Leila Chebaiki; Chemrouk, Naima Chabbi (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2015)
The project to build the Great Mosque of Algiers is underway. This will be the largest mosque in the world, after the mosques at Mecca and Medina. Trying to reflect the Algiers’ context, this project refers in his architectural design to Almoravid (11th century) influences, through an abstract way of interpretation. The aim of this paper is to explain this mode of interpretation by using a new approach. This approach combines both syntactic and semantic categories of the architectural object. It consists on the architectural syntax which tries the combination of space syntax and figurative abstract process. It is through a comparative study between the former mosque of Algiers: Djama’ al-A’dam (AH 490/ AD 1096–1097) and the future great mosque of Algiers that will explain this abstract way of interpretation, which seems more expressive than figurative.